THE IMPACTS OF INTERNATIONAL MIGRATION ON DEVELOPMENT IN INDONESIA: A LITERATURE REVIEW - Anomsari, Endah Tri (EP FEB UNS, 2020)
Remittance often becomes a central point in an analysis of the relationship between migration and development because it is viewed as bringing a positive contribution to development. However, the impact of international migration on development is not reducible to the contribution of remittances. This paper maps the impacts of migration to development, particularly in the Indonesian context. The impacts are categorized into eight different dimensions of development, following the framework. Moreover, the paper explores the level of migration impacts, namely the individual, household, community, and country-level. From the impacts mapping, the paper then critically analyses how to strengthen the impact of migration to development by proposing three main ideas, those are: (1) understanding the complexity of migration flows, (2) acknowledging other forms of remittance and value exchange, and (3) analyzing the institutions surrounding migration-deve-lopment nexus in addition to simply encouraging migrant workers and their families to sustain themselves. Through the analysis, it is known that, even though migration and development are highly complex, the nexus also has potentials that can be explored in the further research agenda. Keywords: development, international migration, remittancesJEL Classification: O15, F22, F24